2021
DOI: 10.1007/s11920-021-01284-2
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–Compulsive Disorder During the COVID-19 Pandemic: a Systematic Review

Abstract: Purpose of Review This systematic review evaluated the impact of the COVID-19 pandemic on obsessive-compulsive symptoms.Recent Findings Most studies showed that obsessive-compulsive symptoms worsened during the early stages of the pandemic, particularly for individuals with contamination-related obsessive-compulsive disorder (OCD), though other symptoms dimensions were found to worsen as well. Many patients and individuals in the general population experienced new obsessive-compulsive-like symptoms centered on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
72
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 70 publications
9
72
0
1
Order By: Relevance
“…Two recent review papers had a much narrower scope than the current study (e.g., Zaccari et al, 2021 considered only clinical samples and Liu et al, 2021 reviewed a much smaller number of papers). The third recent review ( Guzick et al, 2021 ) had a different emphasis from the current study. Our current study proposes to highlight the large scale data focusing on OCD patients and their relationship to usual sources of mental health care during the pandemic, the role of trait compulsivity, what constitutes clinically significant deterioration in OCD, the public health importance of considering the impact of public health messaging on people with OCD, and key areas of focus for future work.…”
Section: Introductionmentioning
confidence: 84%
“…Two recent review papers had a much narrower scope than the current study (e.g., Zaccari et al, 2021 considered only clinical samples and Liu et al, 2021 reviewed a much smaller number of papers). The third recent review ( Guzick et al, 2021 ) had a different emphasis from the current study. Our current study proposes to highlight the large scale data focusing on OCD patients and their relationship to usual sources of mental health care during the pandemic, the role of trait compulsivity, what constitutes clinically significant deterioration in OCD, the public health importance of considering the impact of public health messaging on people with OCD, and key areas of focus for future work.…”
Section: Introductionmentioning
confidence: 84%
“…Extreme focus on hygiene measures and contamination during the COVID-19 pandemic could exacerbate obsessive-compulsive symptoms (Cunning & Hodes, 2022). The COVID-19 pandemic appears to be related with a worsening of obsessive-compulsive symptoms especially during the early stages of the pandemic (Guzick et al, 2021; Maye et al, 2022). Moreover, the COVID-19 pandemic has been an enormous stressor for patients with contamination-related obsessive-compulsive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of infection, germs, contamination, and cleaning compulsions are some of the most frequently reported OCD symptoms ( Abramowitz et al, 2010 , Cordeiro et al, 2015 ). Recent empirical evidence suggests that the onset of the COVID-19 pandemic has been a significant stressor for individuals with OCD and has been associated with increased severity of obsessions and compulsions, particularly, for those with pre-existing contamination symptoms ( Alonso et al, 2021 , Benatti et al, 2020 , Guzick et al, 2021 , Jelinek et al, 2021 , Tanir et al, 2020 ). For instance, several studies have shown increased frequency of obsessions, time spent on compulsive behaviors, higher reported distress and lower perceived controllability over OCD symptoms in OCD patients during the pandemic ( Alonso et al, 2021 , Jelinek et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%